Examining Whiteness in a Children's Centre. (March 2014) - Clarke, Verity; Watson, Debbie
This article utilises critical whiteness theory to explore the ethnic discourses observed in a children's centre in South London. Whilst critical whiteness has been used as a framework to understand race, racism and multiculturalism in a number of settings, including education, there are few studies that have sought to understand ethnicity in early year's contexts in this way. A key focus of the research was to develop child focused methods that captured the perspectives of three- to five-year-olds on ethnicity through photo-elicitation and walking tours. The article explores the multiple ways that whiteness was performed, constructed and deconstructed by the parents, young children and staff in the centre. The article concludes that further explorations of whiteness in early childhood settings are needed in order to develop strategies that will help to produce a version of whiteness that can play a role in the struggle against racism and offer more multicultural early years and family support provisions.